Optimization of H-type Anti-slide Pile Support Structure Based on RSM-NSGA-II - Deng, Yousheng; Zhang, Keqin; Yang, Biao; Li, Long; Zhao, Huiling; Yao, Zhigang (Periodica Polytechnica Civil Engineering, 2024)
The parameters of an h-type anti-slide pile are optimized and analyzed with respect to its structural characteristics. Based on laboratory model tests, further analysis of its stress characteristics is carried out through numerical simulation methods. Then, the response surface methodology (RSM) combined with the NSGAII algorithm was employed to perform multiobjective optimization of the reinforcement performance and engineering cost for h-type anti-slide piles regarding landslide consideration. Finally, the entropy weight TOPSIS method was used for comprehensive evaluation to obtain the optimal structural parameters. The results show that the bending moment distribution of the front and rear rows of h-type piles first increases and then decreases with increasing depth, and the front soil pressure of the pile gradually increases. Using RSM-NSGA-II instead of finite element modeling can shorten the optimization time, and the accuracy of the surrogate model reaches 94.8%. NSGA-II is much stronger than that of the particle swarm optimization algorithm. The entropy weight method combined with the TOPSIS method can obtain the unique optimal solution from the Pareto solution set without prior knowledge. The h-type anti-slide pile with the best structural parameters reduces the cost by 75.19%, while the slope safety factor increases by 47.39%. This method provides a new idea for structural optimization.